Biochemical Study of Bilberry Extract Potential in Preventing Retinal Damage in Rat Model of Diabetes Induced by Streptozotocin/Nicotinamide - Maja Petrović; Marija Trenkić; Marija Veselinović; Aleksandra Smiljković; Dušan Sokolović (Life)
Type 2 diabetes mellitus is a growing global health concern, with diabetic retinopathy (DR) representing a major microvascular complication that contributes significantly to vision impairment. Oxidative stress plays a critical role in the pathogenesis of DR, which is associated with changes in vascularization-associated molecules, such as iNOS, VEGF, and MMP-9. The present study investigates the therapeutic potential of bilberry (Vaccinium myrtillus L.) extract—rich in anthocyanins—applied for 14 days on blood glucose levels, lipid profile, and retinal oxidative stress (lipid peroxidation (TBARS) and advanced oxidized protein products (AOPPs)) in a streptozotocin/nicotinamide (STZ/NA)-induced diabetes rat model. Results showed a significant reduction in non-fasting blood glucose, retinal TBARS, and AOPP levels, and normalization of VEGF and MMP-9 expression in bilberry-treated diabetic rats. Bilberry extract also partially improved lipid profile by lowering LDL levels. However, no significant effects on fasting glucose or serum insulin were observed. These findings suggest that bilberry extract may offer protective effects against oxidative retinal damage and could serve as a complementary approach in managing early diabetic retinopathy.